Dynamics of spike-specific neutralizing antibodies across five-year emerging SARS-CoV-2 variants of concern reveal conserved epitopes that protect against severe COVID-19 - Zayou, Latifa; Prakash, Swayam; Vahed, Hawa; Dhanushkodi, Nisha Rajeswari; Quadiri, Afshana; Belmouden, Ahmed; Lemkhente, Zohra; Chentoufi, Aziz; Gil, Daniel; Ulmer, Jeffrey B.; BenMohamed, Lbachir (Frontiers in Immunology, 2025)
IntroductionSince early 2020, several SARS-CoV-2 variants of concern (VOCs) continue to emerge, evading waning antibody mediated immunity produced by the current Spike-alone based COVID-19 vaccines. This caused a prolonged and persistent COVID-19 pandemic that is going to enter its fifth year. Thus, the need remains for innovative next generation vaccines that would incorporate protective Spike-derived B-cell epitopes that resist immune evasion.MethodsTowards that goal, in this study we (i) Screened the sequences of Spike among many VOCs and identified conserved and non-conserved linear B-cell epitopes; (ii) Compared titers and neutralization antibodies specific to these conserved and non-conserved B-cell epitopes from serum of symptomatic and asymptomatic COVID-19 patients that were exposed to multiple VOCs across the 5-year COVID-19 pandemic, and (iii) Compared protective efficacy of conserved versus non-conserved B-cell epitopes against the most pathogenic Delta variant in a “humanized” ACE-2/HLA transgenic mouse model.ResultsWe found robust conserved B-cell epitope-specific antibody titers and neutralization in sera from asymptomatic COVID-19 patients. In contrast, sera from symptomatic patients contained weaker antibody responses specific to conserved B-cell epitopes. A multi-epitope COVID-19 vaccine that incorporated the conserved B-cell epitopes, but not the non-conserved B-cell epitopes, significantly protected the ACE2/HLA transgenic mice against infection and COVID-19 like symptoms caused by the Delta variant.DiscussionThese findings underscore the importance of conserved B-cell epitopes in generating robust protective immunity against severe COVID-19 symptoms caused by various VOCs, providing valuable insights for the development of broad-spectrum next generation Coronavirus vaccines capable of conferring cross-variant protective immunity.